Planet city - Young, Liam Cole ca. 20./21. Jh; McEoin, Ewan; Gene Buck, Holly; Sassen, Saskia 1947-; Robinson, Kim Stanley 1952-; Toland, Andrew; Hopkinson, Nalo 1960-; Griffen, Ryan; Bratton, Benjamin H. 1968-; Kallis, Giorgos 1972-; Quifan, Chen; Sánchez-Velasco, Amaia; et al. (Uro Publications, 2020)
"Planet City is a project by Los Angeles-based film director and architect Liam Young, exploring the productive potential of extreme densification, in a speculative future where ten billion people surrender the rest of the planet to a global wilderness. It imagines a radical reversal of planetary sprawl, where the world's population retreats from our vast network of cities and entangled supply chains into one hyper-dense metropolis housing the entire population of the earth. It is a vision of the future that runs counter to our current world, where humans dominate the planet. Where centuries of colonisation, globalisation and never-ending economic extraction and expansionism has remade the world from the scale of the cell to the tectonic plate. Although wildly provocative, Planet City eschews the techno-utopian fantasy of designing a new world order. This is not a neo-colonial masterplan to be imposed from a singular seat of power. It is a work of critical architecture - a speculative fiction grounded in statistical analysis, research and traditional knowledge. It is a collaborative work of multiple voices and cultures supported by an international team of acclaimed environmental scientists, theorists and advisors. In Planet City we see that climate change is no longer a technological problem, but rather an ideological one, rooted in culture and politics. This is a fiction shaped like a city. Simultaneously an extraordinary image of tomorrow and an urgent examination of the environmental questions facing us today."--Back cover
Impressum: "Planet City was commissioned by the National Gallery of Victoria for the NGV Triennial 2020"
Keywords: National Gallery of Victoria / Exhibitions; NGV triennial / (2020); National Gallery of Victoria; Urban density; Cities and towns / Growth / Exhibitions; Urban density / Exhibitions; Climatic changes / Exhibitions; Wilderness areas / Exhibitions; Cities and towns / Growth; Climatic changes; Wilderness areas; Verstädterung; Architektur; Globalisierung; Utopie; Exhibition catalogs